Effect of Hydrogen Peroxide on Hydrogen Production from Melon Fruit (Cucumis melo L.) Waste by Anaerobic Digestion Microbial Community - Kharisma, Agung Dian; Amekan, Yumechris; Sarto, Sarto; Cahyanto, Muhammad Nur (International Journal of Renewable Energy Development, 2022)
Biohydrogen (H2) production has the potential to provide clean, environmentally friendly, and cost-effective energy sources. The effect of increasing oxidative stress on biohydrogen production by acid-treated anaerobic digestion microbial communities was studied. The use of varying amounts of hydrogen peroxide (H2O2; 0.1, 0.2, and 0.4 mM) for enhancing hydrogen production from melon fruit waste was investigated. It was found that H2O2 amendment to the H2-producing mixed culture increased hydrogen production. Treatment with 0.4 mM H2O2 increased cumulative H2 output by 7.7% (954.6 mL/L), whereas treatment with 0.1 mM H2O2 enhanced H2 yield by 23.8% (228.2 mL/gVS) compared to the untreated control. All treatments showed a high H2 production rate when the pH was 4.5 â€“ 7.0. Â H2O2-treated samples exhibited greater resilience to pH reduction and maintained their H2 production rate as the system became more acidic during H2 fermentation. The application of H2O2 affected the volatile fatty acid (VFA) profile during biohydrogen fermentation, with an increase in acetic and propionic acid and a reduction in formic acid concentration. The H2O2 treatment positively affects H2 production and is proposed as an alternative way of improving H2 fermentation.